Foliar Application of Leaf Extracts of Glycyrrhiza uralensis Increases Growth and Nutritional Value of Chinese Flowering Cabbage Plants under Field Conditions - Waheed Akram; Sabin Fatima; Tehmina Anjum; Basharat Ali; Guihua Li (Journal of Food Quality)
This study was conducted to explore the effects of ethanolic extracts of leaves of Glycyrrhiza uralensis on the growth and nutritional quality of Chinese flowering cabbage (Brassica rapa subsp. parachinensis) under field conditions. Preliminary greenhouse experiments were carried out with different concentrations of G. uralensis extracts to select the suitable dose for field studies. An extract concentration of 12.5 g/L was selected based on relative growth rate analysis and increase in photosynthetic pigment biosynthesis. Shoot length, shoot fresh weight and dry weight, number of leaves, and marketable value of Chinese flowering cabbage plants were significantly increased in the field trials with foliar application of G. uralensis leaves extracts at a concentration of 12.5 g/L. This biotic elicitor also enhanced the total phenolic and flavonoid contents, with optimal values increasing by 18.76% and 22.43%, respectively, compared with the control under field conditions. The total glucosinolate content was effectively increased (from 11.21 to 15.37 μmol·g−1 DW sinigrin equivalents), particularly 4-methoxyglucobrassicin (from 4.31 to 6.72 μmol·g−1 DW sinigrin equivalents) and glucoalyssin (from 0.14 to 0.19 μmol·g−1 DW sinigrin equivalents) compared with the control plants in field trials. Overall, foliar application of leaf extracts of G. uralensis can markedly increase the growth of Chinese flowering cabbage and enhance its medicinal and nutritional quality in the fields.